Laparoscopic resection of pancreatic neck lesion with Roux-en-Y pancreatico-jejunostomy - Martin Sidler; Pratik Shah; Michael Ashworth; Paolo De Coppi (Elsevier, 2019)
Background: Congenital hyperinsulinism is a rare disease and patients not responding to medical treatment need near-total or partial pancreatectomy, dependent on whether they have diffuse or focal hyperinsulinism, respectively. While laparoscopic technique for distal and for total pancreatectomy has been developed, minimally invasive resection of the pancreatic neck with pancreatico-jejunostomy has not been reported in children before. Case summary: A 2-year old boy suffered from congenital hyperinsulinism, which was refractory to high-dose medical treatment. The nuclear-medicine scan revealed a focal lesion of the pancreatic neck, hence partial pancreatectomy was indicated. On laparoscopy, a slightly prominent tissue mass was apparent in the area of the pancreatic neck. We proceeded with laparoscopic mobilisation of the pancreas from the underlying splenic vessels and resected the pancreatic neck and adjacent parts of the body and the head. After macroscopic resection of the mass, the patient's intraoperative blood glucose levels increased to a point where insulin had to be substituted. To drain the pancreatic tail, we formed an end-to-side anastomosis in the proximal Jejunum and brought the open end to the pancreatic tail and performed a laparoscopic pancreatico-jejunostomy. The patient tolerated the procedure well and had no remaining signs or symptoms of hyperinsulinism. Conclusion: This is the first report of a laparoscopic middle-segmental pancreatic resection with laparoscopic assisted Roux-en-Y pancreatico-jejunostomy in a child. For benign pancreatic lesions proximal to the body and tail, the described minimally invasive technique should be considered.